2022
DOI: 10.1128/aac.00256-22
|View full text |Cite
|
Sign up to set email alerts
|

New Perspectives on Antimicrobial Agents: Imipenem-Relebactam

Abstract: Imipenem (IMI)/cilastatin/relebactam (REL) (I/R) is a novel β-lactam/β-lactamase inhibitor combination with expanded microbiologic activity against carbapenem-resistant non- Morganellaceae Enterobacterales (CR-NME) and difficult-to-treat (DTR) Pseudomonas aeruginosa . Relebactam, a bicyclic diazabicyclooctane, has no direct antimicrobial activity but provides reliable inhibition of many Ambler class A and class C enzymes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 81 publications
0
9
0
Order By: Relevance
“…One of these combinations, imipenem/relebactam, unites imipenem/cilastatin with relebactam, a bicyclic diazabicyclooctane inhibitor of class A and C β-lactamases. 1 Imipenem/relebactam is approved by the EMA and the FDA for hospital-acquired and ventilator-associated bacterial pneumonia (HAP and VAP), bacteraemia associated with HAP and VAP (EMA only), and infections due to aerobic Gram-negative bacilli in adults with limited treatment options [e.g. complicated urinary tract infection (UTI), complicated intra-abdominal infection].…”
Section: Introductionmentioning
confidence: 99%
“…One of these combinations, imipenem/relebactam, unites imipenem/cilastatin with relebactam, a bicyclic diazabicyclooctane inhibitor of class A and C β-lactamases. 1 Imipenem/relebactam is approved by the EMA and the FDA for hospital-acquired and ventilator-associated bacterial pneumonia (HAP and VAP), bacteraemia associated with HAP and VAP (EMA only), and infections due to aerobic Gram-negative bacilli in adults with limited treatment options [e.g. complicated urinary tract infection (UTI), complicated intra-abdominal infection].…”
Section: Introductionmentioning
confidence: 99%
“… 19 , 20 Relebactam is a chemical compound used with imipenem to take role as a β-lactamase inhibitor and it blocks the ability of bacteria to destroy the β-lactam ring. 21 Unfortunately, several studies have shown a concerning uprising in resistance toward this antibiotic resistance. 12 , 13 , 22 …”
Section: Discussionmentioning
confidence: 99%
“…PK/PD targets were 30% fT>MIC for imipenem and free AUC normalized to MIC (at 2 mcg/mL) of ≥8.0 (equivalent to AUC 0–∞ ≥20.52 mcg·h/mL) for relebactam, which is associated with a 2‐log kill in preclinical models; the relebactam concentration is fixed because it does not have intrinsic antibacterial activity. This has been previously described 15,20,23,26–28 …”
Section: Methodsmentioning
confidence: 99%